Calculation of Mesopic Luminance Using per Pixel S/P Ratios Measured with Digital Imaging. Issue 4 (2nd October 2019) - Maksimainen, Mikko; Kurkela, Matti; Bhusal, Pramod; Hyyppä, Hannu
ABSTRACT: This study describes a method of measuring the pixelwise S/P ratio using a calibrated digital camera and applying these S/P ratios to calculate mesopic luminance values. An example of using the developed method is presented. Further improvements for the method are discussed. Graphical Abstract: